Assessing The Financial Feasibility of XYZ Company New Branch - Wihardi, Michael Justin; Lazuardi, Mandra Kitri (Journal of Business and Management, 2019)
Indonesia is the 4th most populous country in the world. The big market size in Indonesia makes Indonesia an attractive target for companies engaged in the food and beverage industry. XYZ company is one of the companies engaged in the food and beverage industry. Seeing the vast market in Indonesia, XYZ company wants to create a new branch in order to reach a wider market. This study aims to assess the feasibility study of the branch to be built by the XYZ Company. Feasibility studies are studies conducted to assess whether a project is profitable to make. This research begins by conducting projections from financial statements to estimate the company's financial condition in the future. This research was made using Capital Budgeting Analysis. The Capital Budgeting Analysis method uses indicators such as Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Period. This study also aims to assess risk in capital budgeting by using sensitivity analysis and simulation analysis. Investment projects carried out by XYZ Company can be categorized as feasible because the Net Present Value (NPV) of the project to be executed is positively valued at IDR 2,691,090,310. In addition, the payback period of the XYZ Company investment project can be achieved within 1 year and 257 days, the period is faster than the maximum return period of 5 years. The Internal Rate of Return owned by XYZ Company is 67%, the value is smaller than the Weighted Average Cost of Capital (WACC) value of 23%. The calculation of sensitivity analysis and simulation analysis shows that the project to be made by XYZ Company has a low risk. It can be seen from XYZ Company’s project investment has a 100% probability above 0. According to the Monte Carlo calculation, the minimum Net Present Value (NPV) obtained by XYZ Company will be IDR 147,329,263 and the maximum NPV obtained is IDR 5,658,991,854 with a mean of IDR 2,900,399,432.